Pengaruh Promosi Kesehatan Menggunakan Leaflet terhadap Tingkat Kecemasan Ibu Selama Perawatan Bayi di RS X Swasta Tangerang - Rianti Simatupang; Paramitha Wirdani NM; Tuti Asrianti Utami (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Introduction: NICU is an intensive care room in a hospital that is specifically provided for newborn babies who experience health problems. Generally, babies are put in the NICU room in the first 24 hours after birth. The psychological pressure that occurs on a baby's parents when the baby is sick is anxiety. Psychoeducational health promotion is one of the nursing interventions that can be carried out on mothers to reduce anxiety. Purpose: The aim of the research is to analyze the effect of health promotion on maternal anxiety levels during baby care in the NICU at Hospital X. Method: This is a quantitative with quasy-experimental study with one group pre test-post test design. This research was carried out at Hospital X, on November-December 2024, with 40 participants. Result: The results showed that the majority were aged 19-35 years (72.5%), had higher education (50.0%), worked (77.5%) and were primiparous (7 50%), with moderate pre-anxiety (50.0%) and mild post-anxiety (50.0%). Paired t-test showed a significant influence of health promotion on the mother's anxiety level during baby care in the NICU at Hospital X (p: 0.000). Conclusion: Health promotion using leaflet may lower maternal anxiety levels in individual with mild to moderate anxiety. It is hoped that nursing services will provide complementary therapies that are appropriate, effective, safe and affordable for patients and can be easily carried out by trained nurses so that they become one of the treatments.